Technological Change and Retirement Decisions of Older Workers - Bartel, Ann P.; Sicherman, Nachum (Journal of Labor Economics, 1993)
According to human capital theory, technological change will influence the retirement decisions of older workers in two ways. First, workers in industries with high rates of technological change will retire later if there is a net positive correlation between technological change and on-the-job training. Second, an unexpected change in the rate of technological change will induce older workers to retire sooner because the required amount of retraining will be an unattractive investment. We matched industry data on productivity growth and occupational data on required training with data from the National Longitudinal Surveys of Older Men to test these hypotheses. Our results support both hypotheses.